(untitled) (International Conference on Education, Psychology and Humanities, 2026)
This article examines the problem of representing the inner experiences of female protagonists in literary translation through the examples of Thomas Hardy’s novel Tess of the d’Urbervilles and Iqbol Mirzo’s novel Bonu. The study considers the preservation of women’s psychological suffering, inner monologues, emotional states, and means of psychological portrayal in the process of translation. The article analyzes how semantic losses, cultural differences, and the translator’s subjective interpretation influence the representation of a female character’s inner world. The results show that the adequate translation of women’s inner experiences requires not only linguistic competence but also gender sensitivity and a deep understanding of cultural context. The article provides a scholarly account of the significance of psychological and gender-oriented approaches in literary translation.